Cold-Triggered Induction of ROS- and Raffinose Metabolism in Freezing-Sensitive Taproot Tissue of Sugar Beet - Keller, Isabel; Müdsam, Christina; Rodrigues, C. Martins; Kischka, Dominik; Zierer, Wolfgang; Sonnewald, Uwe; Harms, Karsten; Czarnecki, Olaf; Fiedler-Wiechers, Karin; Koch, Wolfgang; Neuhaus, H. Ekkehard; Ludewig, Frank; et al. (Frontiers in Plant Science, 2021)
Sugar beet (Beta vulgaris subsp. vulgaris) is the exclusive source of sugar in the form of sucrose in temperate climate zones. Sugar beet is grown there as an annual crop from spring to autumn because of the damaging effect of freezing temperatures to taproot tissue. A collection of hybrid and non-hybrid sugar beet cultivars was tested for winter survival rates and freezing tolerance. Three genotypes with either low or high winter survival rates were selected for detailed study of their response to frost. These genotypes differed in the severity of frost injury in a defined inner region in the upper part of the taproot, the so-called pith. We aimed to elucidate genotype- and tissue-dependent molecular processes during freezing and combined analyses of sugar beet anatomy and physiology with transcriptomic and metabolite profiles of leaf and taproot tissues at low temperatures. Freezing temperatures induced strong downregulation of photosynthesis in leaves, generation of reactive oxygen species (ROS), and ROS-related gene expression in taproots. Simultaneously, expression of genes involved in raffinose metabolism, as well as concentrations of raffinose and its intermediates, increased markedly in both leaf and taproot tissue at low temperatures. The accumulation of raffinose in the pith tissue correlated with freezing tolerance of the three genotypes. We discuss a protective role for raffinose and its precursors against freezing damage of sugar beet taproot tissue.
CRIS-Team Scopus Importer:2021-10-01
Keywords: freezing; pith; raffinose; reactive oxygen species; sugar beet

Multi-omics data integration reveals link between epigenetic modifications and gene expression in sugar beet (Beta vulgaris subsp. vulgaris) in response to cold - Gutschker, Sindy; Corral, José María; Schmiedl, Alfred; Ludewig, Frank; Koch, Wolfgang; Fiedler-Wiechers, Karin; Czarnecki, Olaf; Harms, Karsten; Keller, Isabel; Martins Rodrigues, Cristina; Pommerrenig, Benjamin; Neuhaus, H. Ekkehard; et al. (BMC Genomics, 2022)
BACKGROUND: DNA methylation is thought to influence the expression of genes, especially in response to changing environmental conditions and developmental changes. Sugar beet (Beta vulgaris ssp. vulgaris), and other biennial or perennial plants are inevitably exposed to fluctuating temperatures throughout their lifecycle and might even require such stimulus to acquire floral competence. Therefore, plants such as beets, need to fine-tune their epigenetic makeup to ensure phenotypic plasticity towards changing environmental conditions while at the same time steering essential developmental processes. Different crop species may show opposing reactions towards the same abiotic stress, or, vice versa, identical species may respond differently depending on the specific kind of stress. RESULTS: In this study, we investigated common effects of cold treatment on genome-wide DNA methylation and gene expression of two Beta vulgaris accessions via multi-omics data analysis. Cold exposure resulted in a pronounced reduction of DNA methylation levels, which particularly affected methylation in CHH context (and to a lesser extent CHG) and was accompanied by transcriptional downregulation of the chromomethyltransferase CMT2 and strong upregulation of several genes mediating active DNA demethylation. CONCLUSION: Integration of methylomic and transcriptomic data revealed that, rather than methylation having directly influenced expression, epigenetic modifications correlated with changes in expression of known players involved in DNA (de)methylation. In particular, cold triggered upregulation of genes putatively contributing to DNA demethylation via the ROS1 pathway. Our observations suggest that these transcriptional responses precede the cold-induced global DNA-hypomethylation in non-CpG, preparing beets for additional transcriptional alterations necessary for adapting to upcoming environmental changes.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Abiotic stress; Beta vulgaris subsp. vulgaris; Cold response; DNA methylation; Epigenetics; Omics; RNA-seq; WGBS

Symplasmic phloem unloading and radial post-phloem transport via vascular rays in tuberous roots of Manihot esculenta - Mehdi, Rabih; Lamm, Christian; Bodampalli Anjanappa, Ravi; Müdsam, Christina; Saeed, Muhammad; Klima, Janine; Kraner, Max; Ludewig, Frank; Knoblauch, Michael; Gruissem, Wilhelm; Sonnewald, Uwe; Zierer, Wolfgang (Journal of Experimental Botany, 2019)
Cassava (Manihot esculenta) is one of the most important staple food crops worldwide. Its starchy tuberous roots supply over 800 million people with carbohydrates. Yet, surprisingly little is known about the processes involved in filling of those vital storage organs. A better understanding of cassava carbohydrate allocation and starch storage is key to improving storage root yield. Here, we studied cassava morphology and phloem sap flow from source to sink using transgenic pAtSUC2::GFP plants, the phloem tracers esculin and 5(6)-carboxyfluorescein diacetate, as well as several staining techniques. We show that cassava performs apoplasmic phloem loading in source leaves and symplasmic unloading into phloem parenchyma cells of tuberous roots. We demonstrate that vascular rays play an important role in radial transport from the phloem to xylem parenchyma cells in tuberous roots. Furthermore, enzymatic and proteomic measurements of storage root tissues confirmed high abundance and activity of enzymes involved in the sucrose synthase-mediated pathway and indicated that starch is stored most efficiently in the outer xylem layers of tuberous roots. Our findings form the basis for biotechnological approaches aimed at improved phloem loading and enhanced carbohydrate allocation and storage in order to increase tuberous root yield of cassava.
CRIS-Team Scopus Importer:2019-11-05
Keywords: Apoplast; cassava; CFDA; esculin; morphology; phloem; ray; starch; SUC2; symplast

The large GTPase AtGBPL3 links nuclear envelope formation and morphogenesis to transcriptional repression - Reimann, Theresa; Müdsam, Christina; Schachtler, Christina; Ince, Semra; Sticht, Heinrich; Herrmann, Christian; Stürzl, Michael; Kost, Benedikt (Nature Plants, 2023)
Guanylate binding proteins (GBPs) are prominent regulators of immunity not known to be required for nuclear envelope formation and morphogenesis. Here we identify the Arabidopsis GBP orthologue AtGBPL3 as a lamina component with essential functions in mitotic nuclear envelope reformation, nuclear morphogenesis and transcriptional repression during interphase. AtGBPL3 is preferentially expressed in mitotically active root tips, accumulates at the nuclear envelope and interacts with centromeric chromatin as well as with lamina components transcriptionally repressing pericentromeric chromatin. Reduced expression of AtGBPL3 or associated lamina components similarly altered nuclear morphology and caused overlapping transcriptional deregulation. Investigating the dynamics of AtGBPL3-GFP and other nuclear markers during mitosis (1) revealed that AtGBPL3 accumulation on the surface of daughter nuclei precedes nuclear envelope reformation and (2) uncovered defects in this process in roots of AtGBPL3 mutants, which cause programmed cell death and impair growth. AtGBPL3 functions established by these observations are unique among dynamin-family large GTPases.
CRIS-Team WoS Importer:2023-05-26

Treat and trick: common regulation and manipulation of sugar transporters during sink establishment by the plant and the pathogen - Pommerrenig, Benjamin; Müdsam, Christina; Kischka, Dominik; Neuhaus, H. Ekkehard (Journal of Experimental Botany, 2020)
Sugar transport proteins are crucial for the coordinated allocation of sugars. In this Expert View we summarize recent key findings of the roles and regulation of sugar transporters in inter- and intracellular transport by focusing on applied approaches, demonstrating how sucrose transporter activity may alter source and sink dynamics and their identities. The plant itself alters its sugar transport activity in a developmentally dependent manner to either establish or load endogenous sinks, for example, during tuber formation and filling. Pathogens represent aberrant sinks that trigger the plant to induce the same processes, resulting in loss of carbon assimilates. We explore common mechanisms of intrinsic, developmentally dependent processes and aberrant, pathogen-induced manipulation of sugar transport. Transporter activity may also be targeted by breeding or genetic modification approaches in crop plants to alter source and sink metabolism upon the overexpression or heterologous expression of these proteins. In addition, we highlight recent progress in the use of sugar analogs to study these processes in vivo.
CRIS-Team WoS Importer:2020-08-07

Vernalization alters sink and source identities and reverses phloem translocation from taproots to shoots in sugar beet - Rodrigues, Cristina Martins; Müdsam, Christina; Keller, Isabel; Zierer, Wolfgang; Czarnecki, Olaf; Corral, José María; Reinhardt, Frank; Nieberl, Petra; Fiedler-Wiechers, Karin; Sommer, Frederik; Schroda, Michael; Mühlhaus, Timo; et al. (The Plant Cell, 2020)
During their first year of growth, overwintering biennial plants transport Suc through the phloem from photosynthetic source tissues to storage tissues. In their second year, they mobilize carbon from these storage tissues to fuel new growth and reproduction. However, both the mechanisms driving this shift and the link to reproductive growth remain unclear. During vegetative growth, biennial sugar beet (Beta vulgaris) maintains a steep Suc concentration gradient between the shoot (source) and the taproot (sink). To shift from vegetative to generative growth, they require a chilling phase known as vernalization. We studied sugar beet sink-source dynamics upon vernalization and showed that before flowering, the taproot underwent a reversal from a sink to a source of carbohydrates. This transition was induced by transcriptomic and functional reprogramming of sugar beet tissue, resulting in a reversal of flux direction in the phloem. In this transition, the vacuolar Suc importers and exporters TONOPLAST SUGAR TRANSPORTER2;1 and SUCROSE TRANSPORTER4 were oppositely regulated, leading to the mobilization of sugars from taproot storage vacuoles. Concomitant changes in the expression of floral regulator genes suggest that these processes are a prerequisite for bolting. Our data will help both to dissect the metabolic and developmental triggers for bolting and to identify potential targets for genome editing and breeding.
CRIS-Team Scopus Importer:2020-10-23